Análisis de requerimientos para el desarrollo de una plataforma de Networking para los graduados de la facultad de administración, finanzas e información de la universidad técnica Babahoyo. - Alvarado Páez, Jesús Enrique (2023)
In a global scenario where precarious employment and underutilization of labor resources are critical challenges, Universidad Técnica Babahoyo finds itself immersed in a similar problem. High rates of unemployment and underemployment have a significant impact on its graduates, who struggle to find job opportunities commensurate with their training. To address this, it has proposed to create a special social network for graduates of this school. Its main objective is to connect education with work, helping graduates to collaborate, share knowledge and build professional relationships. The benefits of this idea are not limited to its initial conception. In this study, key stakeholders have been carefully identified, essential functional and non-functional requirements have been delineated, and a solid, multi-faceted rationale for the project has been provided. The benefits of this initiative extend beyond graduates, impacting economic, academic and theoretical domains.